Anti-amyloid monoclonal antibody therapies in Alzheimer’s disease – a scoping review - Shahd Abubaker Elamin (22569539) (2025)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder affecting millions worldwide, and with advancements in the medical field, Anti-amyloid monoclonal antibodies (AA mAbs) targeting amyloid-β have emerged as potential disease-modifying agents altering AD pathology. This scoping review mapped the characteristics, patterns, and gaps in clinical trials investigating the efficacy and safety of AA mAbs in AD treatments, with focus on cognitive, functional, biochemical, imaging, and safety outcomes. It highlighted patterns, gaps, and limitations of the existing literature. A systematic search of PubMed/MEDLINE, Embase, Scopus, and Web of Science was conducted for studies published since inception to February 2022, and eligible studies that investigated efficacy and safety outcomes of AA mAbs in treatment of AD were included. A majority of the included trials reported a combination of cognitive, functional, biochemical, and imaging outcomes. Across the sample, reductions in amyloid burden were frequently reported (10 trials), with a smaller subset of studies reporting significant cognitive and functional improvements (4 trials), primarily lecanemab and aducanumab in addition to one pooled analysis of solanezumab. ARIA-E and ARIA-H were frequently reported among the safety concerns, particularly in high-dose and APOE ε4 carrier populations. Notable limitations were observed in the reviewed literature including a disconnect between biomarker changes and consistent clinical benefits and, importantly, limited population diversity and patient-reported outcomes. This review highlights the need for rigorous, diverse, and patient-centered research. Addressing these gaps is critical in ensuring safe, effective, and equitable treatment for all patients living with Alzheimer’s disease. Other Information Published in: Neuroscience License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://doi.org/10.1016/j.neuroscience.2025.10.011